PERCEPCIÓN DE LOS TRABAJADORES EN EL TELETRABAJO - CASO DE ESTUDIO - Sebastián Pelaez (Revista Ingeniería, Matemáticas y Ciencias de la Información)
In the project, a search sentence was constructed using specific keywords. Using the search, a survey was constructed, thesample obtained was thirty-four people. The results showed that the parts of the body with the greatest discomfort werethe neck, right wrist, lower back, eyes, and head. According to the neck disability index, on average 7.6% indicating noproblems to perform activities. The environmental conditions of working at home, the participants did not identifyproblems, except for the temperature. The RULA results a level of 3 in all cases. A qualitative analysis was conductedidentifying elements such as the chair, desk and use of peripherals that can improve working conditions. Finally, generalrecommendations were made to improve job conditions.